Perceived Injustice Mediates the Relationship Between Perceived Childhood Neglect and Current Function in Patients with Chronic Pain: A Preliminary Pilot Study - Ziadni, Maisa S. (J Clin Psychol Med Settings, 2021)
Cumulative evidence supports the association between perceived childhood neglect and adulthood psychological and physical health. To date, pathways mediating this association remain largely unknown, though other evidence suggests that negative patterns of appraisal, including injustice perception related to pain, may be shaped by prior adverse social experiences. Consequently, the current study examined perceived injustice about chronic pain as a possible factor connecting childhood neglect and pain-related outcomes, given its relevance for both adaptation to chronic pain and to prior adverse life experiences. Patients (n = 742) visiting a tertiary pain clinic completed a survey administered via the Collaborative Health Outcomes Information Registry. Path modeling analyses were used to examine perceived injustice as a mediator of the relationships between childhood neglect and affective distress and physical function, after controlling for pain intensity and pain catastrophizing. Patients endorsing childhood neglect reported higher levels of perceived injustice and worse affective distress and physical function. Further, inclusion of perceived injustice as a mediator fully accounted for the relationship between neglect and current levels of physical function, and accounted for a significant proportion of the relationship between neglect and current levels of affective distress. These preliminary findings suggest that perceived injustice appears to be a more proximal factor by which prior experiences of neglect may adversely affect adaptation to chronic pain. Given the single-item assessment of childhood neglect and cross-sectional nature of the current findings, further research may focus on replicating these findings in longitudinal studies with validated measures and examining other adverse social experiences (e.g., abuse, social disparities) that may contribute to injustice perception and poor pain-related outcomes.